2020
DOI: 10.3390/su13010090
|View full text |Cite
|
Sign up to set email alerts
|

Blockchain-Based Securing of Data Exchange in a Power Transmission System Considering Congestion Management and Social Welfare

Abstract: Using blockchain technology as one of the new methods to enhance the cyber and physical security of power systems has grown in importance over the past few years. Blockchain can also be used to improve social welfare and provide sustainable energy for consumers. In this article, the effect of distributed generation (DG) resources on the transmission power lines and consequently fixing its conjunction and reaching the optimal goals and policies of this issue to exploit these resources is investigated. In order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 176 publications
(72 citation statements)
references
References 39 publications
(41 reference statements)
1
71
0
Order By: Relevance
“…. , N s (3) where in the Equation (3), P Gi (t) and P sj (t) represent the outputs power for ith generator and jth storage at time t.…”
Section: Objective 1: Minimizing the Total Costs Of Operating In Mgmentioning
confidence: 99%
See 1 more Smart Citation
“…. , N s (3) where in the Equation (3), P Gi (t) and P sj (t) represent the outputs power for ith generator and jth storage at time t.…”
Section: Objective 1: Minimizing the Total Costs Of Operating In Mgmentioning
confidence: 99%
“…In addition to this, for consumers, the potential of lower costs, higher reliability of services and power quality, increasing in power efficiency and power independency can be the reasons for higher interests in DGs. Using RESs and green powers, including wind and photovoltaics, can offer notable environmental advantages [1][2][3][4]. In this way, MG can act as a concept that gives an effective solution for integrating renewable DGs into the major power and energy network and offers the requirements of next generation power systems [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…As the outcomes have been shown in articles [28], it was shown that PDM has a significant impact on forecasting the expected customer outage or interruptions' costs. Another important issue that needs to be considered is the growth of distributed generation (DG) in the power grid, which is limited by economic reasons [29][30][31]. Issues such as increasing attention to the quality of electricity and its positive effects on grid-connected equipment, awareness of environmental issues arising from the use of renewable energy, regulation in the electricity market and attention to reducing the cost of photovoltaic and wind production can be defined as the reasons of increasing the integration of DGs in power grid systems.…”
Section: A Backgroundmentioning
confidence: 99%
“…Here S( , ) refers to the share functional amount of members and ; 1 ( , ) and 2 ( , ) donate their hamming distance ( h ) [29,30] and major fitness interval;, respectively; nich radius 1 and 2 refer to the determined maximums of 1 ( , ) and 2 ( , ). Fitness function have been adjusted like below:…”
Section: Global Optimal Solutionmentioning
confidence: 99%
“…Nevertheless, resource allocation for diverse applications at a network edge of dispersed and resource-constrained nodes is difficult [58]. Although blockchain technology is offered to provide secure distributed networks, studying the possibility of combining it into the data replication process would be an exciting subject for further research [59,60].…”
Section: Open Issuementioning
confidence: 99%